Publish or Perish: Research Productivity During Residency Training in Physical Medicine and Rehabilitation. (December 2019) - Bateman, Emma A.; Teasell, Robert
Abstract : Abstract: Research training equips residents with the skills to consume and produce research evidence and deliver evidence-based care. Within Physical Medicine and Rehabilitation, studies have historically demonstrated low rates of resident research productivity. Although Canadian residency requirements mandate research participation, little is known about Canadian residents' research productivity. Using standard systematic review search strategies, we evaluated the rate and type of peer-reviewed publications produced by resident physicians during postgraduate medical training for a historic cohort of Physical Medicine and Rehabilitation residents who successfully passed the Canadian Royal College Fellowship examination in 2015, 2016, and 2017 ( N = 74). Resident physicians produced 62 peer-reviewed publications during the study period. A total of 43.2% of resident physicians produced at least one such publication and 20.3% produced more than one. The resident physician was the first author for 51.6% of publications. Reviews were the most frequent publication type (19.4%), followed by observational studies (16.1%) and case reports (16.1%). Musculoskeletal conditions (11.3%) and stroke (9.7%) were the most frequent areas of study. Most publications were in nonrehabilitation journals. These findings demonstrate modest research productivity despite mandatory research participation; although research productivity is higher than in previous cohorts, publications of convenience, such as reviews and case reports, are similarly frequent.